Internal migration and public opinion about the European Union: a time series cross-sectional study. (3rd August 2018) - Jeannet, Anne-Marie
Abstract: Although the European Union (EU) allows citizens from member countries to migrate freely within its confines to facilitate integration, it may be alienating public support for Europe. This article investigates this by extending group threat theory to explain how internal migration is related to public opinion about the EU using annual Eurobarometer data from 1998 to 2014 across 15 Western European countries. Employing a pooled time cross-sectional design, I find that the presence of EU citizens from Central and Eastern European member states is positively related to public beliefs that EU membership is not beneficial for their country. The results also show that this relationship is even stronger during an economic downturn. There is weak evidence that it may be related to distrust in European institutions as well. These findings shed light on why public support for the EU can erode over time and how it responds to contextual changes in Europe's internal migration patterns. The study concludes by discussing how group threat theory is relevant for understanding public opinion about the EU.